2009
DOI: 10.1002/qre.1012
|View full text |Cite
|
Sign up to set email alerts
|

On t and EWMA t charts for monitoring changes in the process mean

Abstract: The performance of an X-bar chart is usually studied under the assumption that the process standard deviation is well estimated and does not change. This is, of course, not always the case in practice. We find that X-bar charts are not robust against errors in estimating the process standard deviation or changing standard deviation. In this paper we discuss the use of a t chart and an exponentially weighted moving average (EWMA) t chart to monitor the process mean. We determine the optimal control limits for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
79
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 30 publications
(7 reference statements)
1
79
0
Order By: Relevance
“…These charts, intended to monitor the process mean were first proposed by Zhang et al [30], by presenting an X-bar t-chart and a EWMA t-chart. The applicability of these two charts to short production runs was described by Celano et al [9], who also studied their statistical properties.…”
Section: Spc For Short Production Runs -Literature Reviewmentioning
confidence: 99%
“…These charts, intended to monitor the process mean were first proposed by Zhang et al [30], by presenting an X-bar t-chart and a EWMA t-chart. The applicability of these two charts to short production runs was described by Celano et al [9], who also studied their statistical properties.…”
Section: Spc For Short Production Runs -Literature Reviewmentioning
confidence: 99%
“…Unfortunately this is not always the case in practice [20]. Therefore Zhang et al [20] proposed the EWMA t chart to overcome this problem, by showing that the EWMA t chart is more robust than the EWMA X chart in preventing estimation errors or changes in the process standard deviation.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately this is not always the case in practice [20]. Therefore Zhang et al [20] proposed the EWMA t chart to overcome this problem, by showing that the EWMA t chart is more robust than the EWMA X chart in preventing estimation errors or changes in the process standard deviation. In addition, it was shown that the EWMA t chart always has a lower size of the Type II error than the EWMA X chart for mean shifts a[0, 0.5] when the charts are optimally designed for a quick detection of moderate and large shifts (see Figure 7 in Zhang et al [20]).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations